Poverty measurement in Malaysia : a survey of the literature - Mohamed Saladin Abdul Rasool,; Mohd Fauzi Mohd Harun,; Ariffin Mohd Salleh,; Noraini Idris, (Universiti Kebangsaan Malaysia, 2011)
The elimination of widespread poverty and ever growing income inequality are at the core of all development problems and in fact, for many people define the principal objective of development policy. Poverty and inequality need to be measured more precisely to provide a meaningful understanding of how much progress has already been made, how much more remains to be achieved, and how to set incentives for government officials to focus on the most pressing needs. Absolute poverty is defined as the number of people who are unable to command sufficient resources to satisfy their basic needs. Economists have agreed that poverty does not have one definite concept. However, in Malaysia poverty is commonly conceptualised from the perspective of monetary or income. This article outlines the poverty measurement presently used by the Economic Planning Unit (EPU), Prime Minister’s Department. Besides discussing the present poverty line income (PLI) method, the article proposes a multidimensional poverty measurement index. The proposed method comprising of monetary and non-monetary indicators is expected to capture a more realistic poverty group.Furthermore, the multidimensional phenomenon of poverty in a more holistic way is envisaged to be captured and is expected to have an impact on the policy makers as it gives a new perspective for measuring poverty.